(untitled) (Texas Journal of Engineering and Technology, 2022)
The need for rolling stock is established based on the need to assign to each route such a number of buses of a certain passenger capacity, which provides a minimum of the carrier’s costs, provided that the passenger traffic is mastered in compliance with regulatory requirements for the quality of transport services